2014
DOI: 10.3109/13880209.2014.931442
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl acetate extract fromGlycosmis parvaleaf induces apoptosis and cell-cycle arrest by decreasing expression of COX-2 and altering BCL-2 family gene expression in human colorectal cancer HT-29 cells

Abstract: Context: Glycosmis parva Craib (Rutaceae) is reported to have cytotoxic and anti-inflammatory activities by decreasing COX-2 expression. Objective: To investigate the effect of G. parva on human colorectal cancer cells expressing COX-2, HT-29 cells. Materials and methods: HT-29 cells were treated with ethyl acetate extract from the leaves of G. parva (GPE 6.25-100 mg/ml) for 24-72 h. Cell viability was evaluated by the resuzurin reduction assay. An apoptotic study was performed using annexinV/FITC-PI staining.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…There has been a wide consensus that cell apoptosis plays a paramount role in tumor formation and development. Several laboratory studies of both premalignant and malignant tissues have provided evidence that increased expression of COX-2 can facilitate cell proliferation and protect cancer cells from apoptosis, thereby expediting tumor growth ( 27 - 29 ). Inhibition of COX-2 in animal models and epidemiological studies have confirmed its significant implications for cancer treatment or prevention in general.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a wide consensus that cell apoptosis plays a paramount role in tumor formation and development. Several laboratory studies of both premalignant and malignant tissues have provided evidence that increased expression of COX-2 can facilitate cell proliferation and protect cancer cells from apoptosis, thereby expediting tumor growth ( 27 - 29 ). Inhibition of COX-2 in animal models and epidemiological studies have confirmed its significant implications for cancer treatment or prevention in general.…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2 family has two representative members: Bax, which promotes the apoptosis gene, and Bcl-2, which inhibits the overexpression of Bcl-2. Overexpression of Bcl-2 can block cell apoptosis, protecting the cardiomyocytes, while the effect of Bax does the opposite [46]. This study found that the number of apoptotic cells in myocardial tissue increased significantly after MI/IR and the number of apoptosis in the DM-IR group was higher than that in the NDM-IR group and the level of antiapoptotic Bcl-2 protein was significantly lower than that in the NDM-IR group.…”
Section: Discussionmentioning
confidence: 91%
“…It is well known the activation of caspase 3 and caspase 8 is responsible for cell apoptosis [19, 20]. Bcl-2, an anti-apoptotic gene, is reported to be correlated with cell apoptosis and proliferation [21, 22]. Thus, we detected the expression of caspase 3, caspase 8, and BCL-2, when AK027294 expression was significantly knocked down in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 96%